2020
DOI: 10.21203/rs.2.20063/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Population-Based Survey to Assess the Association between Cannabis and Quality of Life among Colorectal Cancer Survivors

Abstract: Background: As more states legalize cannabis for medical and recreational use, people increasingly use cannabis to treat medical conditions and associated symptoms. The prevalence and utility of cannabis for cancer-related symptoms may be clarified by examining cannabis use among patients with a common cancer diagnosis. We aimed to determine the prevalence of cannabis use among colorectal cancer (CRC) survivors and its associations with quality of life (QoL) and cancer-related symptomatology.Methods: A cross-s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Previous studies have investigated the percentage of patients with cancer using cannabis at individual treatment centers and have reported a wide range (16%‐56%) 3‐5 . Our study included a national sample, and we found that 42% of patients with breast cancer were using cannabis.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Previous studies have investigated the percentage of patients with cancer using cannabis at individual treatment centers and have reported a wide range (16%‐56%) 3‐5 . Our study included a national sample, and we found that 42% of patients with breast cancer were using cannabis.…”
Section: Discussionmentioning
confidence: 63%
“…Our study is subject to inherent survey study limitations. Selection biases can result in the overrepresentation of cannabis users, symptomatic patients under treatment with more advanced disease, and residents of states with legalized cannabis 4,6 . Conversely, underreporting of cannabis use can result from its illegal status and social stigma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they fail to put this finding into proper context: the authors note that a prior study reported a 56% prevalence of cannabis use among patients with colorectal cancer 1 . The cited study, in fact, observed a 16% cannabis prevalence, and among the 16% of users, 56%—9% overall—reported using cannabis in the past 30 days 4 . Indeed, with prior studies reporting prevalence estimates ranging from 8% to 24%, the results of the current report are nearly double the upper range of any prior study among general oncology patients 5‐10 or patients diagnosed with cancers at specific anatomic sites 4,11,12 .…”
mentioning
confidence: 96%
“…The cited study, in fact, observed a 16% cannabis prevalence, and among the 16% of users, 56%—9% overall—reported using cannabis in the past 30 days 4 . Indeed, with prior studies reporting prevalence estimates ranging from 8% to 24%, the results of the current report are nearly double the upper range of any prior study among general oncology patients 5‐10 or patients diagnosed with cancers at specific anatomic sites 4,11,12 . To our knowledge, only Pergam et al 8 have reported on cannabis use among patients with breast cancer at a single cancer center in Seattle, Washington, where adult medical and nonmedical cannabis use is legal.…”
mentioning
confidence: 97%